PENGARUH PENGGUNAAN WORDWALL TERHADAP PENINGKATAN KETERAMPILAN MEMBACA SISWA KELAS III SEKOLAH DASAR - Muhajir; Candra; Asriati; Indrawaty; Chadijah Taiyeb, Sitti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explore the effect of using the Wordwall application on improving the reading skills of grade 3 students at SD Negeri 006 Polewali. Using a quantitative approach with a quasi-experimental design, this research involved two groups: an experimental group that used Wordwall and a control group that used conventional learning methods. The results of data analysis show that the average posttest score for the experimental group increased significantly compared to the control group, with an average increase from 60.2 to 75.4 in the experimental group. In addition, the use of Wordwall has been proven to increase student engagement, motivation, and the quality of understanding of the material. The results of the paired sample t-test and independent sample t-test show a significant difference between the pretest and posttest scores in the two groups, supporting the hypothesis that Wordwall is an effective learning tool in improving reading skills. This research concludes that Wordwall can be used as an alternative innovative and interactive learning media to improve elementary school students' reading skills.